Comment on “The breakthrough of philosophy of mind in the construction of artificial intelligence concepts in Marxist philosophy” - Xianxian An (Trans/Form/Ação)
Commented article: LAN, X.; SHU, H. The breakthrough of philosophy of mind in the construction of artificial intelligence concepts in Marxist philosophy. Trans/Form/Ação, Marília, SP, v. 47, n. 6, e02400332, 2024. Available at: https://revistas.marilia.unesp.br/index.php/transformacao/article/view/16279.